2017
DOI: 10.3390/beverages3040056
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS/MS and UPLC–UV Evaluation of Anthocyanins and Anthocyanidins during Rabbiteye Blueberry Juice Processing

Abstract: Blueberry juice processing includes multiple steps and each one affects the chemical composition of the berries, including thermal degradation of anthocyanins. Not-from-concentrate juice was made by heating and enzyme processing blueberries before pressing, followed by ultrafiltration and pasteurization. Using LC-MS/MS, major and minor anthocyanins were identified and semi-quantified at various steps through the process. Ten anthocyanins were identified, including 5 arabinoside and 5 pyrannoside anthocyanins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
(68 reference statements)
3
39
0
Order By: Relevance
“…The identity of the peaks is based on LC-MS/MS data shown in Table 3. [Colour figure can be viewed at wileyonlinelibrary.com] 1999; Skrede et al, 2000;Prior et al, 2001;Howard et al, 2003;Wu & Prior, 2005;Lohachoompol et al, 2008;Barnes et al, 2009;Castañeda-Ovando et al, 2009;Neveu et al, 2010;Fanali et al, 2011;Li et al, 2011Li et al, , 2016aYou et al, 2011;Fibigr et al, 2017;Stein-Chisholm et al, 2017). The identity of eighteen anthocyanins is presented in Table 3 which is similar to those reported for several blueberry cultivars (Yousef et al, 2013).…”
Section: Figuresupporting
confidence: 64%
See 2 more Smart Citations
“…The identity of the peaks is based on LC-MS/MS data shown in Table 3. [Colour figure can be viewed at wileyonlinelibrary.com] 1999; Skrede et al, 2000;Prior et al, 2001;Howard et al, 2003;Wu & Prior, 2005;Lohachoompol et al, 2008;Barnes et al, 2009;Castañeda-Ovando et al, 2009;Neveu et al, 2010;Fanali et al, 2011;Li et al, 2011Li et al, , 2016aYou et al, 2011;Fibigr et al, 2017;Stein-Chisholm et al, 2017). The identity of eighteen anthocyanins is presented in Table 3 which is similar to those reported for several blueberry cultivars (Yousef et al, 2013).…”
Section: Figuresupporting
confidence: 64%
“…. Individual anthocyanins were identified using LC‐QTOF/MS/MS, by comparing the molecular ion (m/z) of each peak and its corresponding fragment ion (MS/MS) with those reported in the database, http://www.plantcyc.org and in the literature (Kalt et al ., ; Skrede et al ., ; Prior et al ., ; Howard et al ., ; Wu & Prior, ; Lohachoompol et al ., ; Barnes et al ., ; Castañeda‐Ovando et al ., ; Neveu et al ., ; Fanali et al ., ; Li et al ., , ; You et al ., ; Fibigr et al ., ; Stein‐Chisholm et al ., ). The identity of eighteen anthocyanins is presented in Table which is similar to those reported for several blueberry cultivars (Yousef et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The largest concentrations of petunidin 3‐glucoside in the CP method (26.93 mg/L) and the low values of this compound were found in the methods using heat (0.45, 0.63, and 0.47 mg/L HP, HB, and VE, respectively. These results are justified by the sensitivity of this anthocyanin to heating (Stein‐Chisholm, Beaulieu, Grimm, & Lloyd, ). In the method with steam (VE), the cyanidin 3‐glucoside, malvidin 3‐glucoside, and delphinidin 3‐glucoside compounds were the main anthocyanins quantified.…”
Section: Resultsmentioning
confidence: 92%
“…Another work, by Stein-Chisholm et al [8] analyzed the impact of rabbiteye blueberry juice processing on phenolic composition, in particular anthocyanin content. Those authors, using LC-MS/MS, identified and semi-quantified the major and minor anthocyanins at various steps of the juice production process.…”
mentioning
confidence: 99%